Prexasertib (LY2606368) reduces clonogenic survival by inducing apoptosis in primary patient-derived osteosarcoma cells and synergizes with cisplatin and talazoparib - Heidler, Christopher L.; Roth, Eva Kathrin; Thiemann, Markus; Blattmann, Claudia; Lopez Perez, Ramon; Huber, Peter E.; Kovac, Michal; Amthor, Beate; Neu-Yilik, Gabriele; Kulozik, Andreas (International journal of cancer, 2019)
Progress in the systemic control of osteosarcoma has been limited over the past decades thus indicating the urgent clinical need for the development of novel treatment strategies. Therefore, we have recently developed new preclinical models to study promising novel agents for the treatment of pediatric osteosarcoma. The checkpoint kinase (chk) inhibitor prexasertib (LY2606368) and its salt form (LSN2940930) have recently been shown to be active in adult and pediatric malignancies, including sarcoma. We have now tested the potency of prexasertib in clonogenic survival assays in two new lines of primary patient-derived osteosarcoma cells and in two established osteosarcoma cell lines as a single agent and in combination with cisplatin and the poly ADP-ribose polymerase (PARP) inhibitor talazoparib. Prexasertib alone results in strongly reduced clonogenic survival at low nanomolar concentrations and acts by affecting cell cycle progression, induction of apoptosis and induction of double-stranded DNA breakage at concentrations that are well below clinically tolerable and safe plasma concentrations. In combination with cisplatin and talazoparib, prexasertib acts in a synergistic fashion. Chk1 inhibition by prexasertib and its combination with the DNA damaging agent cisplatin and the PARP-inhibitor talazoparib thus emerges as a potential new treatment option for pediatric osteosarcoma which will now have to be tested in preclinical primary patient derived in vivo models and clinical studies.
Gesehen am 28.05.2020